Development of Geographic Information System for Government With Extreme Programming and User-Centered Design Methods (Jurnal Bina Praja, 2024)
Software development is among the most powerful needs in every organization and industry in the current generation. It is used to help the functionality of their system by using the software development guide named Software Development Life Cycle (SDLC). Various system developments have been conducted, including developing a public complaint service system. This research applies extreme programming (XP) and User-Centered Design (UCD) development methods to develop the geographic information system for the Badan Narkotika Nasional (BNN) Kediri City complaint service. These development methods are expected to meet user expectations. Also, it can reduce the time required to develop products with results that will be shown by conducting usability testing and validity tests. This research applied extreme programming and user-centered design development methods, both quantitative and qualitative for user testing. The application was successfully developed using XP and UCD development methods. The Kediri City BNN complaint service application was successfully developed in several stages: planning, implementing the design, and program code, followed by the evaluation stage. In the evaluation stage, usability testing results on the geotagging mobile application of the Kediri City BNN complaint service obtained a total score of 92.75% with a very good interpretation, and the validation testing results obtained a value of 100%. Applying extreme programming and user-centered design as a development method produces high usability testing and user experience because, in the development stage, it prioritizes interactions and user opinions.
Keywords: Extreme Programming; User-Centered Design; Geographic Information System; Geotagging